Professor V.Ye. Timonov’s contribution to construction and exploitation of marine ports and hydraulic structures - Soloviova, L. M. (History of science and technology, 2018)
The article deals with the life and activity of V.Ye. Timonov - a prominent Russian scientist-engineer of ways of communications, in particular, considers his contribution to construction and exploitation of marine ports and hydraulic structures. His researches on Odesa marine port and port of Libava have been highlighted in detail. His scientific works were of great interest after be-ing published, especially those touching upon the breakwaters’ construction by means of artificial concrete arrays (first erected on the coast of the Baltic sea by V.Ye. Timonov), as well as those de-scribing organization of the first ground suction works. V.Ye. Timonov being a young engineer was invited for work in «Commission on arranging commercial ports» of Ministry of ways of communi-cations. Analyzing the data on port’s construction in Vladyvostok, yet being built, and the data on already existing and intensively functioning port in Mykolaiv, V.Ye. Timonov came to the conclu-sion about possibilities to improve considerably the turnover of goods in Mykolaiv’s port without charges on constructing new mooring and coastal structures. For this purpose he suggested to im-prove work of moorages, coastal and floating faucets and port elevator. A scientist advised to com-bine necessarily all measures and plans designed and aimed at the development of Odesa and Kherson ports.